Addition of silylated nucleophiles to α-oxoketenes. Issue 14 (19th January 2016) - Dudognon, Yohan; Presset, Marc; Rodriguez, Jean; Coquerel, Yoann; Bugaut, Xavier; Constantieux, Thierry
Abstract : A general evaluation of silylated nucleophiles to intercept transient α-oxoketenes generated by microwave-assisted Wolff rearrangement of 2-diazo-1, 3-dicarbonyl compounds is presented. Abstract : A general evaluation of silylated nucleophiles to intercept transient α-oxoketenes generated by microwave-assisted Wolff rearrangement of 2-diazo-1, 3-dicarbonyl compounds is presented. Original scaffolds and synthetic intermediates are accessed in a rapid, efficient and easy-to-handle way. Mechanistic studies by DFT calculations and some post-functionalizations are discussed.